Perilaryngeal and semiological characteristics of women with odynophonia - Fuentes Aracena, Christopher; Biermann, Christopher; Catrín, Luciano; Zúñiga, Támara (Revista de Investigación en Logopedia, 2021)
The objective of this study is to analyse the perilaryngeal and semiological characteristics of women with odynophonia. With the use of pressure algometry, a numerical scale and a survey subjected to validation and internal consistency processes. 40 female participants were studied. Two groups of 20 subjects each were formed (G1 or asymptomatic group and G2 or group with odynophonia). Pressure pain thresholds (PPTs) for G1 were found between 1000 and 2700 grams, while PPTs for G2 ranged between 500 and 2000 grams (p = 0.000). Sixty (60) percent of participants mentioned that the place with the lowest pressure pain threshold was where pain during the phonation was perceived. In turn, it was observed that odynophonia is a condition that improves with rest; it is mainly accompanied by irritation and itching sensation of the vocal tract; its location tends to be precise and occasionally affects swallowing. Finally, it was observed that the usual intensity of odynophonia is moderate. Pain during phonation is a condition caused by vocal overload and it is accompanied by increased perilaryngeal sensitivity. Women with odynophonia showed specific semiologic and psychosocial characteristics for their condition.
Keywords: Pain; Pressure algometry; Vocal hyperfunction; Vocal semiology